2022
DOI: 10.47405/mjssh.v7i1.1219
|View full text |Cite
|
Sign up to set email alerts
|

Design and Technology in Malaysian Secondary Schools: A Perspective on Challenges

Abstract: Design and Technology (D&T) is a relatively new curriculum in Malaysian secondary schools. The basic idea of a design-based curriculum is to facilitate deeper learning for learners to design and develop knowledge and application. However, knowing how design-based education is employed in schools is crucially essential. Therefore, this study aimed to obtain insights into the D&T curriculum implementation from students and teachers’ viewpoints. The study involved semi-structured interviews with four teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Additional study was undertaken on the make prototype stage of the design process (Ajit, et al 2022;Murphy, et al 2021;Sorby & Panther 2021). Due to a lack of sketching skills, Ajit, Lucas, and Kanyan (2022) observed that the pupils lacked the ability to produce and convey ideas on spatial visualization capacities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional study was undertaken on the make prototype stage of the design process (Ajit, et al 2022;Murphy, et al 2021;Sorby & Panther 2021). Due to a lack of sketching skills, Ajit, Lucas, and Kanyan (2022) observed that the pupils lacked the ability to produce and convey ideas on spatial visualization capacities.…”
Section: Discussionmentioning
confidence: 99%
“…Additional study was undertaken on the make prototype stage of the design process (Ajit, et al 2022;Murphy, et al 2021;Sorby & Panther 2021). Due to a lack of sketching skills, Ajit, Lucas, and Kanyan (2022) observed that the pupils lacked the ability to produce and convey ideas on spatial visualization capacities. The report (Ajit, et al, 2022) with a claim where the students were to present on developing a robot that picks up litter for their prototypes, they noted that the iterative phases of the make prototype stage were difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microcontroller learning approach in Electronic Design often relies on physical hardware, which is expensive and has limitations in terms of deprivation and accessibility in the classroom. In a study of challenges in secondary school D&T subjects, discovered that, in addition to the teachers lack prerequisite knowledge in the topic of Electronic Design, constraints in providing an adequate set of microcontroller for students' use led teachers to teach only theory and not implement projects in class, resulting in students not mastering the basic skills in microcontroller learning and programming [9].…”
Section: 48mentioning
confidence: 99%
“…Lower Secondary (Form 1 to Form 3) and Upper Secondary (Form 4 to 5) are the two secondary education levels. Changes in technological development and the competitiveness of the job market have resulted in modifications to the education system, which now equips younger generations with the necessary knowledge and skills to flourish in the current global economy (Ajit et al, 2022). As a middle-income country, secondary education remains a crucial stage for Malaysia to develop its human capital development before it can establish itself as a knowledge-based economy (Arshad, 2013).…”
Section: Introductionmentioning
confidence: 99%